Impact of bypass diode forward voltage on maximum power of a photovoltaic system under partial shading conditions - Teo J.C.; Tan R.H.G.; Mok V.H.; Ramachandaramurthy V.K.; Tan C. (Elsevier Ltd, 2023)
Diodes; Photovoltaic cells; Solar energy; Solar power generation; By-pass diodes; Forward voltage; Lower voltages; Partial shading; Photovoltaic; Photovoltaic modules; Photovoltaic systems; Worst case scenario; Photovoltaic effects; electrode; photovoltaic system; shading; solar power